Extending the Laundered Funds Destination Theory: Applying the Walker-Unger Gravity Model to Australia-Based Money Launderer Country Preference from 2000-2020 - Woods, Marlon; Roman, Juan; Machuca, Ana; Schaefer, Thomas (International Journal of Business Management and Finance Research, 2025)
The purpose of this study is to determine which countries were the top destinations for laundered funds by Australian-based money launderers between 2000 and 2020. A quantitative methodology using a regression research design was used to assess the attractiveness of each country to Australian-based money launderers during the 2000–2020-time frame. The model findings indicate that Australia, Bermuda, Cayman Islands, French Polynesia, Iceland, Japan, Liechtenstein, Luxembourg, Monaco, New Zealand, Northern Mariana Islands, Norway, Qatar, Singapore, Switzerland, and the United Kingdom were the most appealing countries for Australian money launderers between 2000 and 2020. The results of this inquiry contribute to the existing information on global money laundering patterns by applying the revised Walker-Unger model to ascertain which countries money launderers based in Australia used as funding destinations between 2000 and 2020 and whether there were any changes in the ranks during times of economic slowdown. The revised Walker-Unger model is among the limited number of instruments that can gauge money laundering levels.